The Effect of Implementing an Accounting Information System on Financial Performance - Wardani, Reski; Nisa, Iien Rohmatun; Wiliana, Rahayu (INSIGHT: Indonesian Journal Social Studies and Humanities, 2025)
Abstrak. The study purpose was determine effect of the implementation of accounting information systems on financial performance at the Investment and Integrated Services (DPMPTSP) Pinrang District. The object of research is the Office of Investment and Integrated Services (DPMPTSP) Pinrang District. The analytical tool used is multiple linear regression analysis. The data analysis method used in this research to test the hypothesis is the multiple linear regression analysis method using SPSS 25.0 (Statistical Package for Social Science) software. The results showed that the implementation of accounting information systems can improve financial performance. Indicators of the implementation of accounting information systems namely the use of accounting information systems, the quality of information systems, and convenience of information systems have effect simultaneously on financial performance. Based on the calculation results, it was found that the Accounting Information System Implementation variable had an effect on the Financial Performance at the Investment and Integrated Services (DPMPTSP) Pinrang. The implementation of an accounting information system can improve financial performance, this is in accordance with the results of the F Test which shows that the indicators for Accounting Information System Utilization, Accounting Information System Quality, and Information System Ease have a simultaneous effect on Financial Performance. Kata Kunci: Implementation of Accounting Information Systems, Financial Performance